Formation on of the Cultural Environment of Ukraine through the Development of Creative Clusters - Volkova, Galyna; Tsurkan, Ihor; Diachok, Oksana; Ropetskyi, Volodymyr; Marukhovska-Kartunova, Olga; Маруховська–Картунова, Ольга Олександрівна (MAGNANIMITAS Assn., 2022)
The development of Ukrainian culture embodies the cultural customs, traditions, and national identity of the Ukrainian people. Through the use of territorial united communities functioning in the cultural environment, Ukraine can qualitatively improve the level of the country's brand and ensure the growth of internal culture and Ukrainianization processes. The importance of the issue of creative cluster development lies in the possibility of improving modern Ukrainian culture in the conditions of war and promoting the popularization of culture on the world stage. From the above provisions, the topic of the article requires careful research on the prospects for the formation of creative clusters and the methodology of their formation. It forms the relevance of the research topic. The article aims to study the features of the application of creative clusters and the quality of their use as a tool for the development and formation of the cultural environment in Ukraine. Moreover, it is through the acquisition of current trends in world culture, the formed Ukrainian clusters can be used for the applied analysis of the cultural rise of Ukraine as a result of Russian intervention. The objectives of the article are to determine the characteristic principles of creative cluster development, to study the essence of the concept of creative cluster, and to explore its role in the modern Ukrainian space. The methodology of the study lies in the use of the graphical method. It has served to design the scheme of the system of creative clusters development and implementation of the synthesis method, as well as to reflect the importance of the Ukrainian idea for modern Ukrainian society. The article analyzes the development of digital technologies, their impact on creative clusters, and their functioning both in the global environment and exclusively in the Ukrainian one. The prospects for the development of creative clusters have been investigated and the reasons for their formation have been distinguished. The article provides recommendations for solving the issues of the cultural environment in Ukraine and outlines promising directions for the development of creative clusters. They are aimed at popularizing Ukrainianization in the internal Ukrainian environment and projecting Ukrainian spiritual and ethical morality in the world space.
Keywords: art design; cluster; cultural centers; media technology; national idea; spiritual culture; Ukrainian tradition; Ukrainization